Biji Chia : Karakteristik Gum dan Potensi Kesehatannya - Asep Safari; Feri Kusnandara; Elvira Syamsir (Perum BULOG, 2016)
Chia seeds (Salvia hispanica L.) have distinctive physical characteristics; they are able to form mucilage through hydration process. This mucilage may absorb water up to 12-27 times of dry weight, and have a viscous solution at low concentration. The mucilage of chia seeds has behavior as a non-Newtonian fluid and is classified as an anionic polysaccharide due to its richness in hydroxyl and carboxylate carbonyl groups. For this reason, mucilage of chia seeds is potentially applied as thickeners, stabilizers, emulsifiers, and edible film materials. In addition, chia seeds are reported to contain bioactive compounds and essential fatty acids, especially α-linolenic acid (omega-3). Consuming chia seed can decrease blood cholesterol level, weight gain in obesity, and risk of cardiovascular disease and diabetes. Chia seeds are potentially used for the development of functional foods.